2007
DOI: 10.1080/02770900701645595
|View full text |Cite
|
Sign up to set email alerts
|

Off-Line Fractional Exhaled Nitric Oxide Measurement Is Useful to Screen Allergic Airway Inflammation in an Adult Population

Abstract: To determine whether off-line fractional exhaled nitric oxide (FeNO) measurement is applicable to screen allergic airway inflammation for epidemiologic studies, we examined 280 adults, measuring off-line FeNO samplings, pulmonary function, and serum immunoglobulin E (IgE). Subjects with recurrent wheeze (recurrent wheezers) had significantly higher FeNO and IgE levels and significantly lower forced expiratory volume in 1 second/forced vital capacity (FEV1/FVC) than non-wheezers. Statistical analysis showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
1
12
1
Order By: Relevance
“…NO reacts with superoxides (O·) to form the highly reactive peroxynitrites (ONOO – ) that have been shown to produce airway inflammation7 and cause airway remodelling 8 9. Furthermore, the fractional concentration of NO in exhaled breath, a marker of airway inflammation,10 is predominantly of iNOS origin 11. Increased expression of iNOS may play a role in inflammation of the upper and lower airways, and contribute to both allergic rhinitis and asthma 12…”
Section: Introductionmentioning
confidence: 99%
“…NO reacts with superoxides (O·) to form the highly reactive peroxynitrites (ONOO – ) that have been shown to produce airway inflammation7 and cause airway remodelling 8 9. Furthermore, the fractional concentration of NO in exhaled breath, a marker of airway inflammation,10 is predominantly of iNOS origin 11. Increased expression of iNOS may play a role in inflammation of the upper and lower airways, and contribute to both allergic rhinitis and asthma 12…”
Section: Introductionmentioning
confidence: 99%
“…Strictly, current asthma symptoms on the ECRHS questionnaire are not equal to clinically current symptoms because this questionnaire is designed to detect asthma symptoms over 1 year. Although we must also emphasize that the ROC curve was constructed only to classify subjects of this study and that it was not constructed to help diagnose asthma, a previous study using the same offline method proposed that the optimal cut-off value of FENO was 38.0 ppb for detecting allergic airway inflammation in an adult population [10]. This cut-off value was equal to that we used in this study.…”
Section: Discussionmentioning
confidence: 96%
“…Breath samples were obtained using an offline kit produced by the Center for Environmental Information Science (Tokyo, Japan) to measure F E NO under the same conditions as with online measurement [10,11]. In this device, the expiratory flow rate is adjusted to 50 mL/s when subjects exhale at 1.5 kPa oral pressure after inhaling deeply.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although reasonable agreement has been shown between online and offline measurements [18-20], the measured FeNO values may increase or decrease over time [14,21]. Some investigators found that FeNO levels in the reservoir bag increased after collection [20,22], but others reported that the samples were stable for 24–48 hours [23].…”
Section: Introductionmentioning
confidence: 99%